An Analysis of Students’ Ethical Awareness and Critical Thinking in the Utilization of Artificial Intelligence - Rafiud Ilmudinulloh; Soffan Fatkhulloh; Puput Tri Anggara (Jurusan Tarbiyah dan Pendidikan, 2026)
This study aims to analyze students’ ethical awareness and critical thinking in the utilization of Artificial Intelligence (AI) within academic contexts. The background of this research is rooted in the increasing use of AI tools, such as ChatGPT, which assist students in completing assignments but simultaneously raise issues of ethics, digital plagiarism, and the potential decline of critical thinking. This research employed a descriptive qualitative approach with data collected through questionnaires involving 39 students from the Faculty of Tarbiyah and Teacher Training at IAIN Manado. The instrument consisted of 29 questions covering habits, purposes, ethical awareness, plagiarism, critical thinking, creativity, and tendencies of intellectual laziness. Data were analyzed descriptively using frequencies and percentages, then further interpreted narratively. The findings reveal that all respondents utilized AI, particularly for essay writing, research reports, and presentations. Although 87.2% of students recognized the issue of digital plagiarism, 43.6% still copied AI outputs without paraphrasing or citation, and 30.8% considered AI-generated texts free to use. Furthermore, 41% admitted difficulties in answering critical questions without AI, while 35.9% preferred copy–paste practices over engaging with primary literature. These results highlight AI’s dual role: enhancing productivity while potentially weakening academic ethics, critical thinking, and intellectual independence. The study recommends strengthening digital literacy, integrating ethical education, and adopting pedagogical strategies that balance technological use with the development of students’ independent thinking skills.